Risk Profiles for fall among Elderly People in South India - Satyanarayana Konda; Ravikumar BP; Purushottam A Giri (Medsci Publications, 2018)
Background: Globally, the population of elderly people aged ≥65 years is increasing and is projected to reach 1.5 billion by 2050. In India, the elderly people constitute 8.1% of the total population. Falls are a major health problem in an elderly people and are the second leading cause of accidental or unintentional injury deaths worldwide. Methods: A cross-sectional study was carried out amongst 195 elderly people from March to July 2018 in Khammam District of Telangana State. Data collected includes socio-demographic char- acteristics, fall events, medication use, co-morbidity, visual and hearing impairment, walking aid use, smoking and alcohol con- sumption. For an assessment of functional status, the activities of daily living (ADL) and instrumental activities of  daily  living (IADL) scale were used. Results: A total of 195 elderly people with a mean age of fallers were 68.4±10 years and that of non-fallers were 66.7±5.5 years. The prevalence of falls in the past one year was reported to be 13.8%. Age, gender, comorbidity, visual impairment, living alone  and poor sleep quality were associated with falls. Conclusion: The overall prevalence of fall among elderly was found to be 13.8% with majority of falls in indoor settings. More efforts needed to reduce falls related to home environment with a special focus on elderly people and females.